Chicago Temple Building, Chicago, Clark and Washington Sts, known as... - Auteur inconnu (Wikimedia Commons, 1941)
Carte postale ancienne issue de Wikimedia Commons. Titre: Chicago Temple Building, Chicago, Clark and Washington Sts, known as the 'Skyscraper Church' of... (NBY 415204). Chicago Temple Building, Chicago, Clark and Washington Sts, known as the ' Skyscraper Church ' of French Gotic architecture
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; Histoire Locale; Wikimedia Commons; église; Carte postale